2012
DOI: 10.31274/ans_air-180814-141
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Sulfur Source on Rumen pH and Hydrogen Sulfide Gas Concentration

Abstract: The objective of this experiment was to compare the effects of 5 commonly used sulfur (S) sources in research trials: dry distillers grains with solubles (DDGS), condensed distillers solubles (CCDS), sulfuric acid, sodium sulfate, and calcium sulfate, on ruminal pH and hydrogen sulfide (H 2 S) concentrations. While diet and ruminal pH did differ among the treatments, there was no difference among S sources in ruminal H 2 S concentrations measured 6 hours post-feeding. These data suggest that there is no differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Indeed when the ARPS theory was examined with different sources of S and feeds, Sarturi et al (2013a) reported that ARPS 22 intake (g•steer -1 •d -1 ) accounted for more of the variation in ruminal H 2 S concentrations than total S intake (58 vs. 29%, respectively). Brasche et al (2012) tested the concentration of rumen H 2 S when fistulated steers were fed one of five sources of dietary S in a Latin square design: 40% dry DGS, or additional S from: sulfuric acid, calcium sulfate, sodium sulfate, or condensed corn distillers solubles. Non-DGS S sources were added to the diet to contribute a comparable amount of S as that expected to be in the 40% DGS diet as that expected to come from sulfuric acid in the DGS (as a byproduct of the ethanol production process).…”
Section: Ruminally Available Sulfurmentioning
confidence: 99%
“…Indeed when the ARPS theory was examined with different sources of S and feeds, Sarturi et al (2013a) reported that ARPS 22 intake (g•steer -1 •d -1 ) accounted for more of the variation in ruminal H 2 S concentrations than total S intake (58 vs. 29%, respectively). Brasche et al (2012) tested the concentration of rumen H 2 S when fistulated steers were fed one of five sources of dietary S in a Latin square design: 40% dry DGS, or additional S from: sulfuric acid, calcium sulfate, sodium sulfate, or condensed corn distillers solubles. Non-DGS S sources were added to the diet to contribute a comparable amount of S as that expected to be in the 40% DGS diet as that expected to come from sulfuric acid in the DGS (as a byproduct of the ethanol production process).…”
Section: Ruminally Available Sulfurmentioning
confidence: 99%